PENGEMBANGAN MODUL TEKNIK SMASH BULU TANGKIS BERBASIS APLIKASI ANDROID - Benny Aprial M (Universitas Negeri Medan, 2021)
Abstract : Development of the Andorid Application-Based Badminton Smash Technique Module. The direction and purpose of this research is to seek to develop learning products packaged in android applications in the form of modules or teaching materials for badminton smash, then it is hoped that online learning can now be used by students. In this study, the research used to develop this Android Application Module is R&D (research and development) using the ADDIE Model with 5 main stages of research procedures, namely (A) analysis, (D) design, (D) development, (I) implementation, and (E)valuation. Validation is carried out which aims to determine the suitability and effectiveness of the learning model that will be produced. Based on the results of the assessment from the experts, it can be concluded that the badminton experts obtained 10 and the percentage was 90.91% with a very decent category. Then the expert results from learning obtained a score of 9 with a percentage of 81.81% with a decent category. As for the expert revision, there is absolutely nothing, according to the expert the product is very good. Results from media experts where the acquisition score is 10 and the percentage is 90.91% with a very decent category. As for the expert revision, there is absolutely nothing, according to the product expert, it is very good. The overall results of the expert revision in the large group trial are 29 with an average value of 9.67 and 87.88% for the percentage with a very decent category (used ).Keywords: Module, Smash, BadmintonAbstrak : Pengembangan Modul Teknik Smash Bulu Tangkis Berbasis Aplikasi Andorid. Arah serta tujuan penelitian ini adalah mencari mengembangkan produk pembelajaran yang dikemas dalam aplikasi android berupa modul atau bahan ajar smash bulu tangkis, kemudian diharapkan dalam pembelajaran daring sekarang ini dapat digunakan peserta didik. Pada penelitian ini memilih penelitian pengembangkan Modul Aplikasi Android ini yaitu R&D (research and development) memilih design Model ADDIE dengan prosedur penelitian 5 fase/tahapan : (A)nalysis, (D)esain, (D)evelopment, (I)mplementation, dan (E)valuation. Dilakukan Validasi untuk mengetahui tingkat kelayakan serta keefektifannya dari suaru produk. Penilaian dari para pakar/ahli yaitu dari ahli bulu tangkis diperoleh 10 dan persentase 90,91% dengan kategori sangat layak. Kemudian hasil ahli dari pembelajaran diperoleh skor 9 dengan persentase 81,81% dengan kategori layak. Adapun yang revisi ahli sama sekali tidak ada, menurut ahli produk sudah sangat baik. Hasil dari ahli media dimana skor perolehan 10 dan persentase 90,91% dengan kategori sangat layak. Adapun yang direvisi ahli sama sekali tidak ada, menurut ahli produk sudah sangat baik.. Adapun hasil keseluruhan revisi ahli diuji coba kelompok besar adalah 29 dengan penilaian rata-rata 9,67 dan 87,88 % untuk persentase dengan kategori sangat layak (digunakan). Kata Kunci : Modul, Smash, Bulu Tangkis